Influence of light guide tip used in the photo-activation on degree of conversion and hardness of one nanofilled dental composite - Galvo, M. R. [UNESP]; Costa, S. X. S. [UNESP]; Victorino, K. R. [UNESP]; Ribeiro, A. A.; Menezes, F. C. H.; Rastelli, Alessandra Nara de Souza [UNESP]; Bagnato, V. S.; Andrade, M. F. [UNESP] (Maik Nauka/interperiodica/springer, 2010)
The aim of this study was to evaluate the degree of conversion and hardness of a dental composite resin Filtek (TM) Z-350 (3M ESPE, Dental Products St. Paul, MN) photo-activated for 20 s of irradiation time with two different light guide tips, metal and polymer, coupled on blue LED Ultraled LCU (Dabi Atlante, SP, Brazil). With the metal light tip, power density was of 352 and with the polymer was of 456 mW/cm(2), respectively. Five samples (4 mm in diameter and 2mm in thickness-ISO 4049), were made for each Group evaluated. The measurements for DC (%) were made in a Nexus-470 FT-IR, Thermo Nicolet, E.U.A. Spectroscopy (FTIR). Spectra for both uncured and cured samples were analyzed using an accessory of reflectance diffuse. The measurements were recorded in absorbance operating under the following conditions: 32 scans, 4 cm(-1) resolution, 300-4000 cm(-1) wavelength. The percentage of unreacted carbon double bonds (% C=C) was determined from the ratio of absorbance intensities of aliphatic C=C (peak at 1637 cm(-1)) against internal standard before and after curing of the sample: aromatic C-C (peak at 1610 cm(-1)). The Vickers hardness measurements (top and bottom surfaces) were performed in a universal testing machine (Buehler MMT-3 digital microhardness tester Lake Bluff, Illinois USA). A 50 gf load was used and the indenter with a dwell time of 30 s. The data were submitted to the test t Student at significance level of 5%. The mean values of degree of conversion for the polymer and metal light guide tip no were statistically different (p = 0.8389). The hardness mean values were no statistically significant different among the light guide tips (p = 0.6244), however, there was difference between top and bottom surfaces (p < 0.001). The results show that so much the polymer light tip as the metal light tip can be used for the photo-activation, probably for the low quality of the light guide tip metal.